Management strategies for developing teachers' emotional competency. (1st January 2013) - Cheng, Eric C.K.
This paper aims to explore teachers' emotional competency skills and discusses effective strategies for developing these skills to promote an emotionally intelligent school. This study adopts Bar-On's (1997) theoretical framework to conceptualise emotional competency into developable multifactorial skills and applies his Emotional Quotient Inventory (1997) to collect data from teachers in 40 aided secondary schools in Hong Kong. A total of 958 teachers participated in this questionnaire survey. A six-factor emotional competency model was explored by using a structural equation model. Strategies for developing an emotionally intelligent workplace are recommended to school administrators for promoting an emotionally intelligent school.